2010
DOI: 10.3109/13693780903405774
|View full text |Cite
|
Sign up to set email alerts
|

Indoor wet cells harbour melanized agents of cutaneous infection

Abstract: The biota of black fungi in humid indoor environments was established using a protocol that consisted of non-selective and selective isolation procedures. In total, 113 samples were taken from bathrooms of residences in The Netherlands, Germany and Austria. Samples were processed either (i) directly by culturing on agar media, or (ii) by pre-incubating samples for enrichment in mineral solutions with perlite granules under constant toluene atmosphere for three months. Dilutions from the latter were then cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 43 publications
2
84
0
3
Order By: Relevance
“…Their environmental counterparts usually live in extreme or toxic environments (3)(4)(5). However, only recently we began to realize that black yeast-like fungi are all around in outdoor and indoor, man-made environments, such as railways, bathrooms (6,7), steam baths (8), and dishwashers (9). They are frequently overlooked because they grow slowly, require dedicated isolation methods, and are difficult to diagnose by morphology.…”
mentioning
confidence: 99%
“…Their environmental counterparts usually live in extreme or toxic environments (3)(4)(5). However, only recently we began to realize that black yeast-like fungi are all around in outdoor and indoor, man-made environments, such as railways, bathrooms (6,7), steam baths (8), and dishwashers (9). They are frequently overlooked because they grow slowly, require dedicated isolation methods, and are difficult to diagnose by morphology.…”
mentioning
confidence: 99%
“…Data on morphology of colonies, conidiogenous structures were compared with recent publications (de Hoog et al 2011, Lian andde Hoog 2010).…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…The appearance of human skin infections suggested to be connected with the presence of black yeasts in the rooms, including the bathrooms (i.e. sensu "water systems" rooms) (Lian and de Hoog 2010). These fungi thought to be also associated with many kinds of diseases of wildlife, including fish, marine toads, turtles, shellfish .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…al (2011) have shown that this includes the dishwasher. Actually, most fungi are not dangerous, but some types can be harmful, like oligotrophic black fungi, which have been potential to cause human infection (Lian & de Hoog, 2010), or for example, Exophiala dermatitidis, which can cause potentially fatal systemic and brain infections (Zeng et al, 2007). Furthermore, fungi have also been implicated in the sick building syndrome (Straus, 2009;Thrasher & Crawley, 2009).…”
Section: Introductionmentioning
confidence: 99%